2018
DOI: 10.3390/min8070290
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Characteristics of Nanotubular Halloysites in the Thach Khoan Area, Phu Tho, Vietnam

Abstract: Two types of halloysite collected from the upper (UPS) and lower (LOS) zones of a weathered pegmatite profile in the Thach Khoan area, Phu Tho were defined by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), thermal analysis (TG and DTG), and N 2 adsorption-desorption isotherms. XRD analysis showed that halloysite and kaolinite coexist in samples of size fractions <2 µm. Semi-quantitative analysis by XRD after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
(50 reference statements)
1
7
0
2
Order By: Relevance
“…The adsorption kinetics was studied by two kinetic models: the pseudo-first-order model (equation 6) and the pseudo-second-order model (equation 7): ln(Qe -Qt) = lnQe -k1t (6) t/Qt = t/Qe + 1/(k2. Q 2 e) (7) Where Qe is the adsorption capacity at equilibrium (mg/g), Qt is the adsorption capacity at time t (mg/g). k1 and k2 are pseudo-first-order (1/min) and pseudo-second-order (g/mg/min) rate constants, respectively.…”
Section: Absorption Of Pb 2+mentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption kinetics was studied by two kinetic models: the pseudo-first-order model (equation 6) and the pseudo-second-order model (equation 7): ln(Qe -Qt) = lnQe -k1t (6) t/Qt = t/Qe + 1/(k2. Q 2 e) (7) Where Qe is the adsorption capacity at equilibrium (mg/g), Qt is the adsorption capacity at time t (mg/g). k1 and k2 are pseudo-first-order (1/min) and pseudo-second-order (g/mg/min) rate constants, respectively.…”
Section: Absorption Of Pb 2+mentioning
confidence: 99%
“…Strongly weathered pegmatite bodies provide great potential to form kaolin material in this area. Recently, it is shown that kaolin in Thach Khoan has tabular halloysite, one of the four minerals of the kaolin group [6][7][8]. Thach Khoan halloysites have a tube-shaped structure with an outer diameter size of over 50 nanometers (nm) and lengths of 250-1250 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuy nhiên, trong các nghiên cứu trên, nguyên liệu haloysit dạng ống được sử dụng là nguyên liệu thương phẩm, được mua của các công ty thương mại nên có độ tinh khiết cao và giá mua cao hơn nhiều so với kaolin tự nhiên. Khu vực Thạch Khoán, Phú Thọ được ghi nhận là khu vực có tiềm năng về nguyên liệu kaolin [7][8][9] . Hiện tại, nguồn nguyên liệu kaolin chủ yếu được khai thác sử dụng trong công nghiệp gốm sứ.…”
Section: Giới Thiệuunclassified
“…The mixture was stirred for 3 hours. After that, it was filtered and dried in a Peak 1867.09 cm -1 absorption from OH of water [10]. Peak 1199.72 cm -1 shows the stretching of Si-O-Si [11].…”
Section: Procedures a Adsorbent Preparationmentioning
confidence: 99%